Impact of Social Media on Academic Performance of Grade 6Students (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
Social media is a web-based service that gives an individual the opportunity to create either a public or semipublic profile within a bounded system. In the past year, social media is partly increasing in our daily life, especially in terms of communication, entertainment, and learning for students. Meanwhile, most students use social media for academic performance. It offers innumerable opportunities for learning and collaboration. Most people indicated that social media has brought down and destroyed physical human interaction at an alarming rate and has changed how we view human relationships in this modern time. According to research, people’s level of effect increases, their level of contentment can decrease, and their likelihood of getting in trouble increases. Even the schools have rules not allowing students to use gadgets; hence, parents should not allow their kids to bring any gadget in school. The researchers utilized the descriptive method design for the investigation in collecting information about the impact of social media on the academic performance of Grade 6 students at Caloocan North Elementary School. The researchers purposive sampling to choose 40 students in Grade 6 section 1 at Caloocan North Elementary School as respondents. Given that social media is being used by learners, the respondents were 11–12 years old. The majority of the respondents are female who used their mobile phones to used social media and tend to cheat on their exam because they prefer to use social media than to review for an exam. The commonly used social media platforms among the respondents were Facebook and YouTube; they spent countless hours on these platforms, which turns into an addiction. This study proved that the use of social media does not only have positive impacts on the academic performance of the students; it also has a negative impact that may affect the mental health of students and affect their academic performance.
Keywords: social media, academic performance, healt